(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
Amid the rise of conservative governments and their impacts on LGBT+ bodies, particularly within educational context, this study explored how the strategies of “teacher character” and “composite stimulus” contributed to addressing intersectional issues (gender, sexuality and ethno-racial relations) through a Drama-based process with fifth-grade children in a public school – SC. The research adopted a research-training methodology, drawing on field diary entries, material artifacts created by the children and teacher reflections. Grounded in gender theory, queer, among others, the study is situated within the pedagogical practices of Theatre and Performing Arts in schools.